The image of a homeland in the Polish translations of Miloš Crnjanski’s poetry - Filipek, Małgorzata (Wydawnictwo Uniwersytetu Śląskiego, 2015)
The translations of poems by M. Crnjanski were published in Poland before World War II. Currently, the Polish reader known the volume entitled Lyrics of Ithaca and three poems: Stražilovo, Serbia and Lament over Belgrade. The leitmotif of his poetry is the return to the homeland (Lyrics of Ithaca) and longing for it (poems). In Crnjanski’s poetry the homeland is symbolized by toponyms, whiche are already exhibited in the titles. They present some elements of tradition, e. g. a reference to folk songs (heroes: Prince Marko, Miloš Obilić) and Orthodox religion (churches, icons). The transfer of local names and some elements of foreign culture expose the exotic feature of this territory. It is an example of the cultural barrier and difficulties with understanding cultural context. The poetry by Crnjanski refers to a foreign space (Jan Mayen, Libon, Spain, Tuscany) which is exotic, not only for the Polish reader, but also for readers of the original texts. Преводи песама Милоша Црњанског били су објављивани у Пољској већ пре Другог светског рата. Сада пољски читаоци знају песме из збирке Лирика Итаке, као и три по‑ еме Стражилово, Сербиа и Ламент над Београдом. Лајт мотив ове поезије је повратак отаџбини (Лирика Итаке) и чежња за њом (поеме). Код Црњанског отаџбину симболишу углавном топоними, којих има већ у насловима поема, као и елементи српске традиције — нпр. асоцијације на народне песме и њихове јунаке, као што су Краљевић Марко, Милош Обилић и присуство православља (цркве, иконe). Асоциације на туђу културно‑језичку средину (Париз, Тоскана, Јан Мајен, Шпанија, Лисабон) перципиране су као туђе особине текста и од стране пољских и српских читалаца.